RESEARCH AND DEVELOPMENT MULTIMEDIA PEMBELAJARAN - Lukman A. Irfan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
The article is an attempt to disseminate the research findings titled “the Development of Instructional Multimedia for effective Adolescent to Improve Self Concept and Interpersonal Competency of Adolescent-age orphan”. The research was conducted in Panti Asuhan Yatim Muhammadiyah Lowanu Yogyakarta. The research aimed to develop a training program and training multimedia program for the orphan. The research and development procedures were carried out through ten steps of research and development proposed by Borg and Gall with Training Need Analysis (TNA) approach, since the developed product is training Program and its multimedia. The findings showed that : (1) the quality of the program and multimedia developed is in good and feasible category ; and (2) the developed product can provide motivation, comprehension, significancy, logics of thinking, and especially can improve self-concept and interpersonal competency. It is also able to encourage learning motivation and creativity to invent the orphan talent.